2014
DOI: 10.1080/1463922x.2013.869370
|View full text |Cite
|
Sign up to set email alerts
|

Using a simulated environment to investigate experiences reported during space travel

Abstract: Astronauts report certain experiences that can be classified as awe and wonder when looking out of their space station or shuttle portals at two different stimuli: the earth and deep space. Based on these reports, it was of interest to further investigate those types of experiences by using a mixed-reality environment resembling an International Space Station workstation designed to expose subjects to simulated stimuli of the earth and deep space. The study is multidisciplinary, involving simulation constructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 16 publications
1
18
0
1
Order By: Relevance
“…Of interest to the present study, in recent studies it was found that participants scoring high on absorption were more prone to reporting supernatural experiences in a religious context (e.g., hearing God's voice; [16]) and to report having had an experimentally induced spiritual experience [17]. A recent study reported mixed evidence for the relation between absorption and awe [15]: by using a VR space manipulation, for participants who reported feelings of awe and wonder, both positive and negative correlations with the Tellegen absorption scale were reported. However, the number of participants that was tested in that study was relatively low, thereby limiting the conclusions regarding the relation between absorption and awe.…”
Section: Original Research Reportmentioning
confidence: 94%
See 1 more Smart Citation
“…Of interest to the present study, in recent studies it was found that participants scoring high on absorption were more prone to reporting supernatural experiences in a religious context (e.g., hearing God's voice; [16]) and to report having had an experimentally induced spiritual experience [17]. A recent study reported mixed evidence for the relation between absorption and awe [15]: by using a VR space manipulation, for participants who reported feelings of awe and wonder, both positive and negative correlations with the Tellegen absorption scale were reported. However, the number of participants that was tested in that study was relatively low, thereby limiting the conclusions regarding the relation between absorption and awe.…”
Section: Original Research Reportmentioning
confidence: 94%
“…the tendency to get fully immersed in one's experiences) may predispose people to have self-transcendent experiences [15][16][17], here we investigated the relation between absorption and the experience of awe. That is, we hypothesized that a tendency to get immersed in external stimuli may predispose people to experience awe.…”
Section: Original Research Reportmentioning
confidence: 99%
“…For example, videos of space and nature (Valdesolo & Graham, 2014;van Elk, Karinen, Specker, Stamkou, & Baas, 2016), viewing tall trees in nature (Piff, Dietze, Feinberg, Stancato, & Keltner, 2015), viewing a fossilized skeleton of Tyrannosaurus rex (Shiota, Keltner, & Mossman, 2007), or even just thinking about magnificent and grandiose scenes in nature (Griskevicius, Shiota & Neufeld, 2010;Van Cappellen & Saroglou, 2012) have all been shown to elicit awe. Further, virtual reality technology has been noted to be a strong inducer of awe (Chirico et al, 2017;Chirico, Ferrise, Cordella, & Gaggioli, 2018;Gallagher, et al, 2014) likely because it presents perceptually vast stimuli in an immersive and realistic format.…”
Section: What Causes Awe?mentioning
confidence: 99%
“…Emotional appraisal leading to the experience of awe includes two distinctive elements, namely the feeling of vastness (perceptual or conceptual) and need for accommodation (i.e., the need for updating one's mental schemas to adapt them to the extraordinary). Recent research demonstrated that immersive technologies (e.g., Virtual Reality and 360° immersive videos) can be used to induce profound awe experiences in controlled environments, such as the lab (Gallagher et al, 2014 ; Chirico et al, 2016 , 2017 ; Gaggioli et al, 2016 ). For instance, Chirico et al ( 2017 ) were able to grasp subtle differences in the emergence of awe considering both self-reported and psychophysiological measures of this emotion.…”
mentioning
confidence: 99%